Adsorption behavior of tin phthalocyanine onto the (110) face of rutile TiO2 - Bodek, Lukasz; Engelund, Mads; Cebrat, Aleksandra; Such, Bartosz (Beilstein Journal of Nanotechnology, 2020)
The adsorption behavior of tin phthalocyanine (SnPc) molecules on rutile TiO2(110) was studied by scanning tunneling microscopy (STM). Low-temperature STM measurements of single molecules reveal the coexistence of two conformations of molecules on the TiO2 surface. Density functional theory-based simulations (DFT) indicate that the difference originates from the position of the tin atom protruding from the molecule plane. The irreversible switching of Sn-up molecules into the Sn-down conformation was observed either after sample annealing at 200 °C or as a result of tip-induced manipulation. Room-temperature measurements conducted for a coverage of close to a monolayer showed no tendency for molecular arrangement.
Keywords: rutile (110) surface; scanning tunneling microscopy (STM); tin phthalocyanine (SnPc); titanium dioxide (TiO2)